Comprehending Early Childhood Educators' Knowledge, Attitudes, Practices, and Advocacy for Deep Learning - Cholimah, Nur; Arifiyanti , Nurul; Ningrum , Eka Sapti Cahya; Tjiptasari , Fitriana; Christianti , Martha; Hayati , Nur; Maharani, Oktaviana (Journal of Education Culture and Society, 2026)
Aim. The goal of this study was to look into how early childhood educator feel about deep learning, including their knowledge, attitudes, practices, and support for it. Methods. This research employed a cross-sectional quantitative survey with 5,580 non-formal early childhood education instructors in Yogyakarta Province, Indonesia. We used an 18-item structured questionnaire to collect data. It asked about four areas: awareness of deep learning, attitudes and interest in implementation, deep learning–based teaching techniques, and hurdles and support for implementation.Results. These results show that even while people have positive attitudes and are very interested, there are still practical problems. To use deep learning effectively, schools need to support it, teachers need to get professional development that is relevant to their work, and the curriculum needs to be in line with it.Conclusions. Support from school leaders and educational institutions is crucial to close the gap between theory and practice and make sure that new ways of teaching are used successfully in early childhood education.